Nonadherence in Home-Based Pulmonary Rehabilitation Program for COPD Patients - Yi Li; Hongyu Qian; Kewei Yu; Ying Huang (Canadian Respiratory Journal)
Background. The pulmonary rehabilitation (PR) is beneficial for COPD patients. Due to the poor rate of adherence, we evaluate the factors which will predict the nonadherence of PR. Method. We analyzed the data from a retrospective study of COPD patients who were enrolled to attend the PR program. Patients were classified as the adherence group and the nonadherence group according to completion of over 50% sessions during the 8-week PR program. Demographic characteristics, 6-minute walking distance (6MWD), COPD assessment test (CAT), modified Medical Research Council scale (mMRC), and emotional function were compared between two groups. Univariate and multivariable analyses were performed to determine the factors of poor adherence of PR. Results. Among 418 patients, 170 patients (40.7%) who completed less than 50% sessions of the PR program were categorized as “nonadherence.” Compared to completers, “nonadherence” patients had more cigarette consumption, higher emotional score, less 6MWD, more exacerbation, using nebulizer frequently, and higher rate of smoking at enrollment. On multivariate analysis, more exacerbation frequency (odds ratio (OR) = 1.434, 95% confidence interval (CI): 1.191∼1.796, P=0.046) and smoking at enrollment (OR = 3.349, 95% CI: 1.194∼6.302, P=0.012) were predict factors associated with nonadherence of PR. Conclusion. COPD patients with frequent exacerbation and smoking currently were more likely to be nonadherence during PR.